2015
DOI: 10.1002/tea.21251
|View full text |Cite
|
Sign up to set email alerts
|

Families support their children's success in science learning by influencing interest and self‐efficacy

Abstract: How is a child's successful participation in science learning shaped by their family's support? We focus on the critical time period of early adolescents, testing (i) whether the child's perception of family support is important for both choice preferences to participate in optional learning experiences and engagement during science learning, and (ii) whether the effects on choice preferences and engagement are mediated through effects on child interest and self‐efficacy in science. Structural equation modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 71 publications
7
79
0
1
Order By: Relevance
“…Friedel, Cortina, Turner, and Midgley () found that seventh grade students' perceptions of their parents' goals emphases were good predictors of the students' personal goal orientation in mathematics. Sha et al () reported that “early adolescents' perceived family support for learning is associated with their choices for and engagement in science learning, and that these effects are mediated by effects on child interest and self‐efficacy in science” (p.450). Turner et al () found that perceived parental support for pursuing math and science careers predicted young adolescents' math self‐efficacy.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Friedel, Cortina, Turner, and Midgley () found that seventh grade students' perceptions of their parents' goals emphases were good predictors of the students' personal goal orientation in mathematics. Sha et al () reported that “early adolescents' perceived family support for learning is associated with their choices for and engagement in science learning, and that these effects are mediated by effects on child interest and self‐efficacy in science” (p.450). Turner et al () found that perceived parental support for pursuing math and science careers predicted young adolescents' math self‐efficacy.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…There is a shortage of skilled scientists, engineers, and technicians (European Commission, ; National Research Council, ) fueled in part by a well‐recognized decline in students' interest, motivation, and engagement in science learning beginning at early adolescence (Vedder‐Weiss & Fortus, , ). Among a wide array of factors, research has shown that school plays a primary role in the development of students' motivation to learn science (Bottia, Stearns, Mickelson, & Moller, ; Schunk, Meece, & Pintrich, ; Sha, Schunn, Bathgate, & Ben‐Eliyahu, ). Although relationships between school learning, career orientations, and eventual career choices are fuzzy, it appears that the pursuit of science, technology, engineering and mathematics (STEM) learning throughout the school years is a necessary condition for an eventual career in STEM (Lent & Brown, ; Wang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Parents who encourage after‐school science involvement or get involved in children's homework, express their views about science directly or behaviorally, and share more time with their children (and thus carry more influence with their children) than teachers. As with teachers, parents’ beliefs and goals broadly impact children and their achievement (Ceglie & Setlage, ; Sha, Schunn, Bathgate, & Ben‐Eliyahu, ; Villegas & Lucas, ). For example, children with performance‐oriented parents are more likely to have performance goals themselves (Gonida, Kiosseoglou, & Voulala, ).…”
Section: Parent and Teacher Influences On Science Learning And Achievmentioning
confidence: 99%
“…Students' perception of science difficulty and the extent to which they believe they can successfully meet this difficulty are factors relevant to their science self‐efficacy. Researchers argue that students' science achievement and belief in their efficacy to succeed in science influences their choices of science‐related activities, how much effort they invest in those activities, and how long they persist in the face of difficulty (Bandura, ; Britner & Pajares, , ; Morgan, Farkas, Hillemeier, & Maczuga, ; Sha, Schunn, Bathgate, & Ben‐Eliyahu, ; Zeldin & Pajares, ). Therefore, science achievement and self‐efficacy in science—as predictors of students' willingness to take science courses and subsequent course performance—remain important factors in students' science participation (Andre et al, ; Britner & Pajares, ; Kupermintz, ; Lau & Roeser, ).…”
Section: Science Achievement Motivation and Everyday Relevancementioning
confidence: 99%